INFILTRATION OF ISRÂILIYYÂT STORIES AND MAWḌÛ‘ÂT IN TAFSÎR FATḤ AL-QADÎR BY AL-SHAWKÂNÎ - Atabik, Ahmad (Jurnal Studi Ilmu-ilmu Al-Qur'an dan Hadis, 2020)
The commentators of the Qur’anic exegesis agree that the infiltration of the biblical stories (isrâ’îliyyât) and mawḍû‘ât in various commentaries is an indisputable fact. Since the exegesis of the Qur’an was recorded up to now, dozens of credible commentaries have been produced. However, after having been carefully examined, it turns out that most of those commentaries include isra'iliyyat and mawdu‘at. This article aims to identify the infiltration of isrâ’îliyyât and mawḍû‘ât in Tafsir Fatḥ al-Qadîr by al- Shawkânî. This study uses qualitative methods with library research techniques. To deepen the data analysis, this research uses the hermeneutic approach. This research found that in al- Shawkânî’s exegesis, he included two narrations of isrâ’îliyyât, namely about the story of Harut and Marut, and the exegesis of sakinah by the People of the Book (Ahl al-kitab). However, he gave criticism and notes to these two narrations. Meanwhile, in mawḍû‘ât narrations, al- Shawkânî inserted three mawḍû‘ât hadiths about Ali ibn Abi Talib’s cult into his interpretation. But unfortunately, al- Shawkânî gave neither any notes nor criticism of the three narrations. It seems that Al- Shawkânî was still influenced by the Zaydi Shii sect even though in another work entitled, al-Fawâ’id al-Majmu‘ah fî al-Ahâdîth al- Mawḍû‘ah, he explained that the three narrations were included in mawḍû‘ or fictitious.